2017
DOI: 10.1177/1471301217703242
|View full text |Cite
|
Sign up to set email alerts
|

Montessori-Based Activities Among Persons with Late-Stage Dementia: Evaluation of Mental and Behavioral Health Outcomes

Abstract: Objectives Literature regarding Montessori-based activities with older adults with dementia is fairly common with early stages of dementia. Conversely, research on said activities with individuals experiencing late-stage dementia is limited because of logistical difficulties in sampling and data collection. Given the need to understand risks and benefits of treatments for individuals with late-stage dementia, specifically regarding their mental and behavioral health, this study sought to evaluate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 49 publications
0
45
1
1
Order By: Relevance
“…It was found that this method improved the quality of life of the elderly with dementia. Contrary to the results of the present study, Wilks (2019) (17) observed that the Montessori method significantly reduced the individuals' psychological well-being, social interactions, and capacity for daily activities. However, it caused a slight increase in the quality of life and a slight decrease in anxiety and problematic behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…It was found that this method improved the quality of life of the elderly with dementia. Contrary to the results of the present study, Wilks (2019) (17) observed that the Montessori method significantly reduced the individuals' psychological well-being, social interactions, and capacity for daily activities. However, it caused a slight increase in the quality of life and a slight decrease in anxiety and problematic behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Adjust the diet reasonably to meet the nutritional intake, strengthen exercise, strengthen body resistance, and promote the metabolism. Finally, health education and nursing should be carried out, and patients and their families should be actively taught disease-related knowledge and nursing methods, so as to promote the effective treatment for patients and reduce the risk of bad behavior and mental health outcomes [11].…”
Section: Treatmentsmentioning
confidence: 99%
“…However in another relevant study, Montessori based activity was not proven effective on problem behaviors diminished in severe dementia patients. [ 5 ] The inconsistent outcomes on agitation may lead to confusing understanding of the efficacy of Montessori-based activity in dementia patients. Moreover, the majority of studies enrolled patients with small sample size (<100 patients), which may limit the reliability of the conclusions.…”
Section: Introductionmentioning
confidence: 99%